30 Development of a mobile app 'Hear me out' to support Audiology patients. (30th November 2020) - Bosch, Max; James, Jason; Rothwell, Lucy; Bassi, Daiana; Conner, Sue; Fu, Yun; Mohamedally, Dean; Molyneux, Gemma; Roberts, Graham; Sebire, Neil J; Chorbachi, Raouf; Stephenson, Natalie
Abstract : Transition into adult services can be a challenging time, where young patients are very quickly expected to take responsibility for their own medical care. Studies have shown that transition can be linked to a decline in health, as patients struggle to cope with the stresses and demands that go with the change from paediatric to adult services. In order to support children through transition, GOSH launched 'Growing Up, Gaining Independence' support programme. To further develop the support available through this programme, the Audiology team designed a mobile app aimed at patients preparing to transition into adult care. As part of a joint collaboration between GOSH and UCL computer science (CS) through the industry exchange network, the prototype mobile app 'Hear Me Out' was developed using Ionic. In addition, a content management system was developed using NodeJS, with a MySQL database to allow content delivered via the app to be to edited and updated. The mobile app provides helpful information to patients and families, including features such as 'MyStory' that allows patients to log important events such as appointments or symptoms. The app has support in the form of a glossary to help patients to understand medical terminology and includes information on NHS support services that provide further patient support. The app is ready to be trialled with patients and families, to gather feedback on how the design and content can be improved. This app is an example of how technology can be developed to support children and young people gain independence and manage their medical care with confidence.